Analyzing driving forces behind changes in energy vulnerability of Spanish electricity generation through a Divisia index-based method. (1st March 2015) - Fernández González, P.; Moreno, B.
Highlights: We propose and develop the LMDI approach to factorize changes in electricity bill vulnerability. Spanish vulnerability (1995–2011) markedly grew mainly by increasing gas dependence. Fuel price increase and growing importance of electricity damage energy security. Energy intensity advances & fuel diversification: insufficient to drive vulnerability. Main recommendation: enhance internal energy market and common external EU strategy. Abstract: High energy dependence on fossil raises vulnerability concerns about security of supply and energy cost. This research examines the impact of high dependence of imported fuels for power generation in Spain through the quantification and analysis of the driving forces behind the change in its electricity bill. Following logarithmic mean Divisia indexes approach, we present and perform a new method that enables a complete decomposition of changes in electricity vulnerability into contributions from several drivers. In fact, we identify five predefined factors behind the variations in vulnerability in Spain during the 1998–2011 period: fuel price, average heat rate, fuel dependence, degree of electricity importance and energy intensity. The application of this approach reveals a significant increase in Spanish vulnerability in the last two decades, promoted by increments in fuel price and importance of electricity over the primary energy consumption, but especially by increasing fuel dependence (particularly gas dependence). Therefore, findings mainly advocate for those strategies aimed at reducing Spanish energy dependence. Also those improving thermal efficiency and energy intensity are indicated.